2014
DOI: 10.1007/s11240-014-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture and aromatic profile in Salvia dolomitica Codd

Abstract: In this study, we developed tissue culture protocol of Salvia dolomitica, a particularly fragrant sage and we evaluated the yield and the profile of essential oil (EO) produced from plants grown in vivo compared to in vitro plant material cultured in two light intensity growth conditions. Plant extracts secreted from glandular trichomes are, in Lamiacea, a valuable source of biologically active volatile compounds. Microscopical observations permitted to\ud describe, for the first time, secretory structures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…The S. sclarea EO evidenced results in partial agreement with those observed by Aćimović and co-workers [34] on clary sage EO from Tajikistan. The S. dolomitica EO was a subject of discord, in fact, Kamatou et al [35] and Bassolino et al [36] found a composition similar to what we found in the current study, while in a more recent study by Ebani [33], eucalyptol was the main compound. Caser underlined a completely different profile where limonene (19.8%), δ-3-Carene (9.1%), and germacrene D (8.6%) dominated together with (E)-β-ocimene (7.39%) and β-caryophyllene (7.9%) [37].…”
Section: Discussionsupporting
confidence: 89%
“…The S. sclarea EO evidenced results in partial agreement with those observed by Aćimović and co-workers [34] on clary sage EO from Tajikistan. The S. dolomitica EO was a subject of discord, in fact, Kamatou et al [35] and Bassolino et al [36] found a composition similar to what we found in the current study, while in a more recent study by Ebani [33], eucalyptol was the main compound. Caser underlined a completely different profile where limonene (19.8%), δ-3-Carene (9.1%), and germacrene D (8.6%) dominated together with (E)-β-ocimene (7.39%) and β-caryophyllene (7.9%) [37].…”
Section: Discussionsupporting
confidence: 89%
“…Taxa of Salvia spp. (sage) are mainly aromatic plants, rich in essential oils (EOs) and widely employed in foods, perfumery and cosmetics [ 1 ]. EOs from Salvia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other substrates such as soil (inside the bottles) could be used as an alternative model of plant growth, leading to new possibilities for investigation. The most recent literature describes in vitro studies of VOCs using SPME techniques leading to difficult quantitative interpretations or using destructive methods such as incubation of the harvested tissue at a non‐biological temperature followed by headspace analysis . The glass chamber set‐up was based on preliminary tests focusing on the size of the cuvette system, the development‐age pattern of the plantlets (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, in vitro headspace analysis in connection with abiotic stress studies is usually performed under laboratory conditions. A number of studies described in recent literature have used methods involving plant biological sample destruction such as volatile extraction under air‐dried conditions at 40°C for 72 h, or hydrodistillation performed from cut plant materials . We therefore decided to develop a glass collection chamber that would not harm the plant during its in vitro physiological development or during the VOC sampling procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation